Competitive strategy of food industry - Berseneva, Anna; Vlasenko, Ludmila (My University, 2014)
Competitiveness measures the capacity to keep and gain market shares in domestic and international markets in a competitive environment. Nevertheless, one should bear in mind that the trade surplus of one country spells the trade deficit of another. The quest for competitiveness is therefore intrinsic to all private businesses, and on a larger scale, this quest involves entire sectors of activity and countries. An economic agent may only be qualified as competitive in comparison with other competitors offering the same type of goods or services. If average prices allow covering the production costs, including minimum remuneration for fixed production factors the player in question is deemed to be competitive.
Keywords: food industry; production costs; competitiveness; витрати виробництва; конкурентоспроможність; харчова промисловість; пищевая промышленность; издержки производства; конкурентоспособность; кафедра ділової іноземної мови та міжнародної комунікації